MODERN TREND OF THE GRAVITATIONAL WAVE DETECTION - Rudenko, V. N. (Одеські астрономічні публікації, 2017)
A brief review of the gravitational wave detection is presented and some modern approach in the gravitational wave experiment is considered. In addition to the old method of searching for coincident reactions of two separated gravitational antennae it was proposed to seek perturbations of the gravitational detector noise background correlated with astrophysical events such as neutrino and gamma ray bursts which can be reliably registered by correspondent sensors. The problem of optimal algorithms for this approach is discussed. The importance of the question is demonstrated in reanalysis of the old data concerning the phenomenon of neutrinoravity correlation registered during of SN1987A explosion.